Twenty years of merit-pay Programme in Argentinean universities: Tracking policy change through instrument analysis - Sarthou, Nerina (2016)
In the 1990s, one of the major concerns related to university performance in Argentina was how to encourage academics to increase knowledge production, the new central economic commodity in a global market. Therefore, in 1994 a unique faculty merit-pay programme, based on peer evaluation, was introduced: The Incentive Programme for Research professors of Public Universities. Although it has been in place for twenty years without any interruption, it is not the same policy instrument as it was 20 years ago, when first implemented, and this is a key reason for its continuity. This paper adopts a methodology based on the assumption that three attributes of policy instruments could help recognise policy change: The actors targeted, the incentives used to enrich policy objectives and the economic resources mobilised. While in its beginnings the programme was characterised as an important way of accessing funds, twenty years later the acquisition of prestige and academic power has increased its importance. This transformation explains why it remains in place today, and was not abolished with the change of government in 2003.